Maintenance of aerobic or resistance training after an exercise intervention among breast cancer patients after neoadjuvant chemotherapy - Goldschmidt, Siri; Schmidt, Martina; Rosenberger, Friederike; Wiskemann, Joachim; Steindorf, Karen (Journal of physical activity and health, 2023)
Background: Exercise interventions have been shown to be beneficial for cancer patients regarding various treatment-related side effects and quality of life. For sustainable effects, patients should continue the training. Therefore, we investigated the maintenance of an exercise training in breast cancer patients, reasons for (dis)continuation, and explored possible influencing factors. Methods: The investigation is based on a 3-arm randomized intervention trial comparing aerobic and resistance training (19 [4]) during or after neoadjuvant chemotherapy among breast cancer patients. About 2 years after breast surgery, 68 patients (age 52 [11] y) provided information about training continuation, self-reported reasons of (dis)continuation, sociodemographics, employment status, age, and body mass index. Training continuation was investigated with Kaplan-Meier analyses. Results: The intervention was rated as good or very good by 88.1% of participants. Nevertheless, 52.9% discontinued the training directly, but half of them changed to different types of exercise. Reasons for discontinuation included lack of time and long travel distance to the training facility. The median continuation was 19.0 months (Q1, Q3: 5.5, 36.0) with no statistically significant difference between the intervention groups. Younger, better educated, partnered patients tended toward longer training continuation. Conclusions: The majority of patients continued exercising after the end of intervention. However, a nonnegligible number discontinued training immediately or after few months. Practical, social, and financial support for a transition to an adequate training that is affordable and feasible in the patient’s daily life might foster training maintenance. Especially patients who are less educated, elderly, or living alone may need more support to continue exercising.
Gesehen am 05.12.2023